VD_FINDINFO Jug / 2020 / 227 vom 24. Februar 2020 - VD Tribunal cantonal (2020)
CONSTATATION DES FAITS, FIXATION DE LA PEINE, COMMERCE DE STUPÉFIANTS, CONFISCATIONDROIT PÉNAL | 47 CP, 69 CP, 70 CP, 10 CPP (CH)